Cirrhosis Hampers Early and Rapid Normalization of Natural Killer Cell Phenotype and Function in Hepatitis C Patients Undergoing Interferon-Free Therapy - Perpiñán, Elena; Pérez-Del-Pulgar, Sofía; Londoño, María-Carlota; Mariño, Zoe; Bartres, Concepción; González, Patricia; García-López, Mireia; Pose, Elisa; Lens, Sabela; Maini, Mala K.; Forns, Xavier; Koutsoudakis, George (Frontiers in Immunology, 2020)
Background: Chronic hepatitis C virus (HCV) infection impairs natural killer (NK) cell phenotype and function. Whether restoration of NK cells occurs after successful interferon (IFN)-free therapies remains a controversial issue. Aim: To analyse how HCV-related liver cirrhosis impacts on changes in NK cells prior and post IFN-free therapies. Methods: NK cell analysis by multicolour flow cytometry was performed in HCV-infected patients with (n=17) and without (n=14) cirrhosis at baseline, week 4 during therapy and weeks 12 and 48 after the end-of-therapy (FU12 and FU48, respectively). Cirrhotic non-HCV patients (n=12) and healthy individuals (n=12) served as controls. Results: At baseline, HCV-cirrhotic patients presented an altered distribution of NK subsets (CD56dim and CD56bright) with higher expression of NKp46, HLA-DR, NKp30, KIR2DL2/L3, NKG2A and CD85j receptors compared to healthy controls. All frequencies normalized by FU48, except for CD85j+ cells. Likewise, substantial alterations were detected in NK cell function assessed by (i) signal transducer and activator of transcription (STAT1) and phosphorylated levels of STAT1 and STAT4, (ii) degranulation (CD107a), (iii) cytotoxicity (tumor-necrosis-factor-related apoptosis-inducing ligand expression, TRAIL), and (iv) cytokine production (IFN-γ and tumor-necrosis factor-α, TNF-α). Of note, NK cell function at FU48 remained partially impaired. By contrast, non-cirrhotics showed normal baseline frequencies of HLA-DR, NKG2A and CD85j-expressing NK cells. Importantly, altered baseline frequencies of NK cell subsets and NKp46+ CD56dim cells, as well as NK cell function, were rapidly and completely restored. Conclusions: NK cell phenotype alterations persist after HCV eradication in cirrhotic patients, while their function is only partially restored, compromising immune restoration and immunosurveillance.